Efektifitas Keputusan Manajemen Dalam Penilaian Kinerja Karyawan Menerapkan Metode Weigthed Product (WP) - Tri Widayati; Nugroho Sumarjiyanto Benedictus Maria (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Performance appraisal of employees is an important thing to do by government agencies and private companies. It is useful to see, monitor the level and quality of work given by an employee to his company in order to create a company that is able to achieve the goals of each company by starting to do evaluation of HR (Human Resources) because in the business and management world says that a great company is a company that is able to manage its human resources. In employee performance appraisal, each company has their own way and certainly different in the actual practice of employee performance appraisal activities must be done properly and fairly as possible to eliminate social gaps in the world of work and reduce the occurrence of errors in granting an assessment of the performance of each each company employee and the results obtained after employees are given an assessment of their performance are expected to grow and influence the level of loyalty given by employees to the company and foster high self-motivation for the progress of the company itself. In evaluating employee performance, there are several tools that can be used, one of which is a decision support system that will process some of the criteria set by the company using the Weighted Product (WP) method